The Influence Of Core Values AKHLAK "Amanah, Competent, Harmonic, Loyal, Adaptive, Collaborative" On Employee Motivation Of Pt Pupuk Sriwidjaja Palembang - Tien Yustini; Juhaini Alie; Tri Maradona Fajar Putra (Syntax Literate, 2022)
This research was aimed to investigate the impact of the attitude of trustful, competent, harmonious, loyal, adaptive and collaborative on the employee’s motivation partially as well as simultanously. The method used in this research was descriptive quantitative by using multiple linear regression analysis. The population in this research was all employee of PT Pupuk Sriwidjaja Palembang. There were 145 persons taken as the sample that was determined by using slovin equity. The data was analyzed by using instrument analysis (validity and reliability test), regression test (multiple linear regression, correlation coefficient and determination) and hypotheses analysis (t test and F test). The data was analyzed in terms of normality analysis, multicolinearity test and heteroscedastisity test as well. The result of the research showed that the t value of each variable (trustful, competent, harmonious, loyal, adaptive and collaborative) > t distribution table, so there was a significant influence of each attitude on the the employee’s motivation, and the t value of harmonious < t tabel so there was no a significant influence on the the employee’s motivation, the F value of (trustful, competent, harmonious, loyal, adaptive and collaborative) > F table so there was a simultaneous significant influence on the the employee’s motivation.